Pengembangan Media Pembelajaran Berbasis Web Google Sites pada Pembelajaran IPS Kelas V SDN Cinangka 5 Depok - Lidya Syahrani; Rudy Gunawan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Because educators play a pivotal role in the educational process, they must be resourceful and innovative when developing lesson plans that use various forms of learning material. Because social studies is often considered a lesson with a lot of theory and children often become bored in such classes, engaging and high-quality learning material is essential for social studies instruction in primary schools. Students are more likely to pay attention in class when their teachers use engaging learning media to convey information that pique their interest. The goal of this research is to help students better grasp social studies concepts and to get them involved in class so that they may learn relevant material via the creation of authentic learning media on Google Sites. This research made use of the ADDIE methodology, which includes the following five steps: analysis, design, development, implementation, and evaluation. A number of options are available inside Google Sites for online education, including Home, Fundamental Competencies, Attendance, Content, and Games. findings indicated that students' replies about Google Sites learning media were 94.25%, validation findings from media experts were 92% with a